2015
DOI: 10.3389/fpsyg.2015.01383
|View full text |Cite
|
Sign up to set email alerts
|

How do different components of Effortful Control contribute to children’s mathematics achievement?

Abstract: This work sought to investigate the specific contribution of two different components of Effortful Control (EC) -attentional focusing (AF) and inhibitory control- to children’s mathematics achievement. The sample was composed of 142 children aged 9–12 year-old. EC components were measured through the Temperament in Middle Childhood Questionnaire (TMCQ; parent’s report); math achievement was measured via teacher’s report and through the standard Woodcock–Johnson test. Additionally, the contribution of other cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 119 publications
(201 reference statements)
2
19
0
Order By: Relevance
“…The study of early temperament manifestations in children with FXS is critical, as it provides information regarding individual differences in emotional processing and behavioural repertoire that set the stage for later-appearing symptoms/behaviour problems (Gartstein et al 2012), as well as cognitive functioning (Wolfe & Bell 2007;Eisenberg et al 2010;Sánchez-Pérez et al 2015). A number of temperament frameworks have been proposed (e.g.…”
mentioning
confidence: 99%
“…The study of early temperament manifestations in children with FXS is critical, as it provides information regarding individual differences in emotional processing and behavioural repertoire that set the stage for later-appearing symptoms/behaviour problems (Gartstein et al 2012), as well as cognitive functioning (Wolfe & Bell 2007;Eisenberg et al 2010;Sánchez-Pérez et al 2015). A number of temperament frameworks have been proposed (e.g.…”
mentioning
confidence: 99%
“…Some evidence has shown that effortful control is positively associated with student engagement, including emotional engagement (Valiente, Lemery‐Chalfant, & Castro, ), cognitive engagement (Blair & Razza, ), and behavioral engagement (M. Wang et al, ). In addition, effortful control is typically associated with math ability (Blair, Knipe, & Gamson, ; Sánchez‐Pérez, Fuentes, Pina, López‐López, & González‐Salinas, ; Swanson et al, ; Zhang & Rao, ). It suggests that effortful control may be important in improving mathematical abilities through the active engagement in math learning activities.…”
Section: The Present Studymentioning
confidence: 99%
“…Participants were recruited through two state primary schools in Murcia, Spain, as part of a wider study [20][21][22] . The primary sample comprised 137 Spanish children, aged 7-12 years (2 nd -6 th grade).…”
Section: Participantsmentioning
confidence: 99%